2015
DOI: 10.5826/dpc.0503a10
|View full text |Cite
|
Sign up to set email alerts
|

Feily’s method as a new mode of hair grafting in prevention of scalp necrosis even in dense hair transplantation

Abstract: Hair restoration is a safe procedure and most of its associated complications are preventable by the surgeon and/or the patient. Recipient area necrosis is rare but arises when an increased number of recipient grafts are utilized and de-vascularization of the scalp occurs. The aim of this study was to investigate and compare all cases and pictures reported in main search engines and Iranian centers of hair transplant to find the dangerous zone of necrosis and to provide a new method for prevention of necrosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Predisposing ingredients are diabetes mellitus, smoking, atrophic skin damage, preexisting recipient‐site scarring, or prior scalp surgery (Konior, ). Potential technical factors associated with the recipient‐site necrosis are large openings, mega‐sessions, dense packing, epinephrine solutions injected directly into the recipient site, and deep slitting (Feily & Moeineddin, ; Konior, ; Loganathan et al, ; Nusbaum & Nusbaum, ). It has been suggested that darkness can be a warning of sudden scalp necrosis and may outline potential danger zones (Feily & Moeineddin, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Predisposing ingredients are diabetes mellitus, smoking, atrophic skin damage, preexisting recipient‐site scarring, or prior scalp surgery (Konior, ). Potential technical factors associated with the recipient‐site necrosis are large openings, mega‐sessions, dense packing, epinephrine solutions injected directly into the recipient site, and deep slitting (Feily & Moeineddin, ; Konior, ; Loganathan et al, ; Nusbaum & Nusbaum, ). It has been suggested that darkness can be a warning of sudden scalp necrosis and may outline potential danger zones (Feily & Moeineddin, ).…”
Section: Discussionmentioning
confidence: 99%
“…Potential technical factors associated with the recipient‐site necrosis are large openings, mega‐sessions, dense packing, epinephrine solutions injected directly into the recipient site, and deep slitting (Feily & Moeineddin, ; Konior, ; Loganathan et al, ; Nusbaum & Nusbaum, ). It has been suggested that darkness can be a warning of sudden scalp necrosis and may outline potential danger zones (Feily & Moeineddin, ). Accordingly, appropriate rest and re‐perfusion time is the key point of prevention of scalp necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occasionally, very nervous patients faint or feel faint during the procedure, but this can be managed by simple measures such as lowering the head between the knees or laying the patient in a prone position [16].…”
Section: Syncopementioning
confidence: 99%
“…Occasionally, for extensive areas of necrosis, scalp expansion may be required for repair. In the treatment of tissue necrosis, hair transplantation can be performed after recovering tissue necrosis [16].…”
Section: Necrosismentioning
confidence: 99%